The Adoption of Mobile Technology for Learning in Public Universities in Ogun State, Nigeria - Adegboyega S. OYEWOLE; Anu K. Toriola; Adekunle A. Adebayo; Sururat O. Shabi; Iyoho O. Edith (Al-Hijr: Journal of Adulearn World, 2022)
This study examines the characteristics that influence undergraduate students in public universities in Ogun State to use mobile learning technologies. Based on primary data collected using self-designed questionnaire, the study explored the effect of undergraduate students' perceived satisfaction, perceived ease of use, and perceived accessibility on the use of mobile devices in the classroom, as well as whether there is any difference in undergraduate students' perceptions of the usefulness of mobile technology for learning based on sex and age. Data from a random sample of 400 students from two public colleges in Ogun State was analyzed using the regression Analysis of Variance (ANOVA) technique. Undergraduate students' evaluations of satisfaction, ease of use, and accessibility have been found to have a direct impact on the usage of mobile technology for learning in public universities. Furthermore, it was discovered that, while age and gender have no significant joint and independent influence on the use of mobile technology for learning in public universities, undergraduate students' perceptions of accessibility, satisfaction, and ease of use have a positive significant joint and independent influence. The study discovered that undergraduate students' evaluations of satisfaction, ease of use, and accessibility encourage them to adopt mobile technology for studying in public universities in Ogun State. Undergraduates should be encouraged by obtaining, providing, or funding mobile learning technologies, according to the study. A section for M-learning applications should also be created to provide students with a visual and auditory tutorial.